Pneumatosis Intestinalis in the Setting of COVID-19: A Single Center Case Series From New York - Miyara, Santiago J.; Becker, Lance B.; Guevara, Sara; Kirsch, Claudia; Metz, Christine N.; Shoaib, Muhammad; Grodstein, Elliot; Nair, Vinay V.; Jandovitz, Nicholas; McCann-Molmenti, Alexia; Hayashida, Kei; Takegawa, Ryosuke; et al. (Frontiers in Medicine, 2021)
This case series reviews four critically-ill patients infected with SARS-CoV-2 (COVID-19) suffering from pneumatosis intestinalis (PI) during their hospital admission. All patients received the biological agent tocilizumab (TCZ), an interleukin (IL)-6 antagonist, as an experimental treatment for COVID-19 before developing PI. COVID-19 and TCZ have been independently linked to PI risk, yet the cause of this relationship is unknown and under speculation. PI is a rare condition, defined as the presence of gas in the intestinal wall, and although its pathogenesis is poorly understood, intestinal ischemia is one of its causative agents. Based on COVID-19’s association with vasculopathic and ischemic insults, and IL-6’s protective role in intestinal epithelial ischemia-reperfusion injury, an adverse synergistic association of COVID-19 and TCZ can be proposed in the setting of PI. To our knowledge, this is the first published, single center, case-series of pneumatosis intestinalis in COVID-19 patients who received tocilizumab therapy.